Acute Ethanol Exposure Increases the Susceptibility of the Donor Hearts to Ischemia/Reperfusion Injury after Transplantation in Rats - Li, Shiliang; Korkmaz, Sevil; Loganathan, Sivakkanan; Weymann, Alexander; Radovits, Tamás; Barnucz, Enikő; Hirschberg, Kristóf; Hegedüs, Peter; Zhou, Yan; Tao, Liang; Páli, Szabolcs; Veres, Gábor; et al. (PLOS ONE, 2012)
Background Many donor organs come from youths involved in alcohol-related accidental death. The use of cardiac allografts for transplantation from donors after acute poisoning is still under discussion while acute ethanol intoxication is associated with myocardial functional and morphological changes. The aims of this work were 1) to evaluate in rats the time-course cardiac effects of acute ethanol-exposure and 2) to explore how its abuse by donors might affect recipients in cardiac pump function after transplantation. Methods Rats received saline or ethanol (3.45 g/kg, ip). We evaluated both the mechanical and electrical aspects of cardiac function 1 h, 6 h or 24 h after injection. Plasma cardiac troponin-T and glucose-levels were measured and histological examination of the myocardium was performed. In addition, heart transplantation was performed, in which donors received ethanol 6 h or 24 h prior to explantation. Graft function was measured 1 h or 24 h after transplantation. Myocardial TBARS-concentration was measured; mRNA and protein expression was assessed by quantitative real-time PCR and Western blot, respectively. Results Ethanol administration resulted in decreased load-dependent (−34±9%) and load-independent (−33±12%) contractility parameters, LV end-diastolic pressure and elevated blood glucose levels at 1 h, which were reversed to the level of controls after 6 h and 24 h. In contrast to systolic dysfunction, active relaxation and passive stiffness are slowly recovered or sustained during 24 h. Moreover, troponin-T-levels were increased at 1 h, 6 h and 24 h after ethanol injection. ST-segment elevation (+47±10%), elongated QT-interval (+38±4%), enlarged cardiomyocyte, DNA-strand breaks, increased both mRNA and protein levels of superoxide dismutase-1, glutathione peroxydase-4, cytochrome-c-oxidase and metalloproteinase-9 were observed 24 h following ethanol-exposure. After heart transplantation, decreased myocardial contractility and relaxation, oxidative stress and altered protein expression were observed. Conclusions These results demonstrate acute alcohol abuse increases the susceptibility of donor hearts to ischemia/reperfusion in a rat heart transplant model even though the global contractile function recovers 6 h after ethanol-administration.